2009
DOI: 10.1563/aaid-joi-d-09-00035.1
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Width of Keratinized Mucosa on the Health Status of the Supporting Tissue Around Implants Supporting Overdentures

Abstract: Our objective was to determine the association between keratinized mucosa width and the health status of the supporting tissue around implants supporting overdentures. Sixty-six functioning dental implants were examined. Periodontal parameters measured included gingival index, plaque index, bleeding on probing, probing depth, mucosal recession, periodontal attachment level, radiographic bone level, and width of keratinized mucosa. A negative correlation was found between keratinized mucosa width and mucosal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
157
1
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(177 citation statements)
references
References 33 publications
9
157
1
10
Order By: Relevance
“…In the systematic review by Brito et al 13 the authors found three studies [21][22][23] showing higher index rate of bleeding in implants with keratinized tissue width around implants measuring less than 2mm. Adibrad et al 24 reported that the absence of an appropriate keratinized tissue area around the implant presents significantly larger buildup biofilm scores, gingival inflammation, bleeding on probing as well as marginal recession.…”
Section: Discussionmentioning
confidence: 99%
“…In the systematic review by Brito et al 13 the authors found three studies [21][22][23] showing higher index rate of bleeding in implants with keratinized tissue width around implants measuring less than 2mm. Adibrad et al 24 reported that the absence of an appropriate keratinized tissue area around the implant presents significantly larger buildup biofilm scores, gingival inflammation, bleeding on probing as well as marginal recession.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Bu çalışmada da kanama yüzdeleri karşılaştırıldığında plak skorları ile benzer şekilde KDG ≤ 2 mm olan grupta kanama skorlarının KDG>2 mm olan gruptan anlamlı şekilde fazla olduğu gösterilmiştir. Bu farkın plak birikiminden kaynaklandığı düşünülmektedir.…”
Section: Grafik 6 İmplant çEvresi Dişeti Sağlığına Göre Gruplara Dağunclassified
“…22 Çalışmalarda keratinize doku bandı genişliği 2 mm'den az olan bölgelerde mukozitis gelişme oranının daha fazla olduğu ortaya konmuştur. 10,11,15,23 Bu durum, yeterli keratinize doku bandı genişliği bulunmayan implantların çevresinde plak kontrolünün yeterli şekilde uygulanamaması sonucu mikrobiyal dental plağa bağlı gelişen enflamatuvar yıkımdan kaynaklanmaktadır. Çalışmanın bulguları değerlendirildiğinde diğer çalışmalarla benzer şekilde mukozitis ve peri-implantitis görülme sıklığının KDG ≤ 2 mm olan grupta daha fazla olduğu gözlenmiştir.…”
Section: Grafik 6 İmplant çEvresi Dişeti Sağlığına Göre Gruplara Dağunclassified
See 2 more Smart Citations